Pan's labyrinth [videorecording (Blu-ray)] - Toro, Guillermo del, 1964-; Toro, Guillermo del, 1964-; Toro, Guillermo del, 1964-; Baquero, Ivana, 1994-; López, Sergi, 1965-; Verdú, Maribel, 1970- (Criterion collection, 2016)
Set in post-civil war Spain, a young girl flees the home of her cruel step-father into an underground fantasy world where she encounters a strange creature and a terrifying battle between good and evil.